Co-digestion of oat straw and cow manure during anaerobic digestion: Stimulative and inhibitory effects on fermentation. (December 2018) - Zhao, Yubin; Sun, Fanrong; Yu, Jiadong; Cai, Yafan; Luo, Xiaosha; Cui, Zongjun; Hu, Yuegao; Wang, Xiaofen
Graphical abstract: Highlights: Cow manure (1/3) functioned as a stimulant during oat straw anaerobic digestion. Addition of cow manure affected methane yield more than the total solids content. C/N ratio = 27 was suitable for anaerobic digestion of oat straw waste and cow manure. Higher methane yields were due to the increasing degradation of cellulose. Clustering analysis provided significant guidance for demonstrating project process. Abstract: Impacts of adding different amounts of cow manure (CM) on the anaerobic digestion (AD) of oat straw (OS) with total solids content (TS) values of 4%, 6%, 8% and 10% was assessed over 50 days using batch experiments. A modified Gompertz model was introduced to predict the methane yield and determine the kinetic parameters. The optimum addition was a 1:2 ratio of CM to the OS added, which resulted in a suitable C/N ratio of 27 and a higher degradation rate of lignocellulose. The best cumulative methane yield of 841.77 mL/g volatile solids added (VSadded ) was 26.64% greater than that of digesting OS alone. In addition, the amount of CM added produced larger effects than that of changes in the TS. However, higher CM concentrations were found to be inhibitory. Clustering analysis could provide significant guidance for demonstrating project process and combining farming and animal husbandry.